Políticas públicas de educação para povos indígenas no Brasil: transformações conceituais e legais - Marchetti, Cristiane Teixeira Bazilio [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Considerando que os povos indígenas do Brasil, desde o início de suas relações sociais com os não-indígenas, foram perdendo parte significativa de sua identidade originária, por meio de processos violentos (para além da violência física, a cultural sobre sua essência e a estrutural sobre os seus direitos e políticas públicas), e considerando a importância dos processos de produção de conhecimento escolar na articulação complexa de saberes, a presente dissertação de mestrado traz um estudo acerca das políticas públicas de educação indígena no Brasil, em seu percurso histórico e legal. A pesquisa está situada no contexto da vida rural no qual a maioria das aldeias indígenas brasileiras estão instaladas. Nesse sentido, o objetivo principal desta pesquisa está em descrever as transformações do processo histórico de produção das atuais políticas públicas de educação indígena no Brasil, desde os primórdios da colonização europeia à Constituição Federal de 1988, que se tornou o marco principal das políticas públicas que hoje existem.

Considering that the indigenous peoples of Brazil, since the beginning of their social relations with non-indigenous peoples, were losing a significant part of their original identity, through violent processes (in addition to physical violence, cultural about its essence and structural about their rights and public policies), and considering the importance of processes of production of school knowledge in the complex articulation of knowledge, this master's thesis brings a study about the public policies of indigenous education in Brazil, in its historical and legal course. The research is situated in the context of rural life in which most brazilian indigenous villages are installed. In this sense, the main objective of this research is to describe the transformations of the historical process of production of current public policies of indigenous education in Brazil, from the beginnings of European colonization to the Federal Constitution of 1988, which became the main landmark of public policies that exist today. Thus, we sought to build a response to the central problem that is circumscribed in "how did the transformations of the historical process of production of the current public policies of indigenous education in Brazil take place?" The methodological proposal was based on a descriptive research, under a qualitative approach, within a historiographical perspective, establishing itself on the techniques of bibliographic exploration and documentary exploration, taken as complementary to a good study on the subject and its transformations. The transformations of the historical process of production of current public policies took place in a slow and painful process. The legislation snaging indigenous school education was gradually developed thanks to the greater prominence of the Amerindian peoples themselves, but these laws are still following their course and the right to a differentiated education is gradually won through many subsequent struggles and legislations. This research can be used as a basis in the perspective in which it will sustain other scientific works that can be carried out with theoretical-empirical methodological wingspan, corroborating for improvements in this process.
Public education policies for indigenous peoples in Brazil: conceptual and legal transformations
Keywords: Escolas indígenas; Public Policies; Políticas públicas